2022
DOI: 10.4103/jfmpc.jfmpc_497_22
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to post-exposure prophylaxis among animal bite patients – A hospital-based epidemiological study

Abstract: Background and Objectives: Although rabies is a 100% fatal disease, it is preventable with appropriate and timely post-exposure prophylaxis (PEP). A hospital-based study was conducted among 360 animal bite patients in the Anti-Rabies Clinic (ARC) of Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi (VMMC and SJH). Materials and Methods: A predesigned, pretested, structured questionnaire was administered by the interview technique to assess the complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…In our current study, we observed a predominance of male individuals, constituting approximately three-fourths (280, 65.3%) of the study population. These findings align with previous investigations conducted by Khokar 15,17,18 These discrepancies can likely be attributed to variations in the characteristics of the study populations and the specific geographical contexts in which the studies were conducted. The study conducted by Panda and Kapoor was done in a tertiary care hospital, so more category III patients might have sought care.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our current study, we observed a predominance of male individuals, constituting approximately three-fourths (280, 65.3%) of the study population. These findings align with previous investigations conducted by Khokar 15,17,18 These discrepancies can likely be attributed to variations in the characteristics of the study populations and the specific geographical contexts in which the studies were conducted. The study conducted by Panda and Kapoor was done in a tertiary care hospital, so more category III patients might have sought care.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study revealed a preponderance of participants below the age of 30 years, a pattern consistent with the findings reported by Kinge and Supe, Ganasva et al, and Gadekar and Dhekale [12][13][14]. Similarly, the majority of bites (318, 74.1%) in our study were attributed to dogs, which is in accordance with the observations reported in a study conducted by Panda and Kapoor 15. In the present study, a significant proportion of cases were categorized as category II (74.8%) and category III (15.6%), accounting for a cumulative total of 90.4% of cases.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have mostly explored the adherence of rabies-exposed patients seeking PEP and rabies vaccination in areas where medical resources are scarce or in rural areas [ 15 , 16 ]. However, studies have shown that residents of urban areas in China have poor knowledge of rabies and that compliance with PEVs among rabies-exposed patients in urban areas is suboptimal [ 17 , 18 ]. This study combined the characteristics of animal injury occurrence and the level of rabies prevention knowledge, attitude, and practice (KAP) in rabies-exposed patients, aiming to illustrate the factors influencing adherence to PEV by rabies-exposed patients throughout the standardized process in Shenzhen and to provide data support and theoretical basis for improving rabies vaccination adherence among urban residents and standardizing the PEP and disposal process of rabies.…”
Section: Introductionmentioning
confidence: 99%